Impact of Self Help Groups on Socio-economic Status of Dairy Farmers in Kamrup District of Assam - Rahman, Saidur; Gupta, Jancy (Indian Journal of Hill Farming, 2018)
A study was conducted to assess the impact of Self Help Group activities on the socioeconomic status of dairy farmers in Kamrup district of Assam. From twenty randomly selected dairy Self Help Groups, 100 members were selected randomly and 100 nonmembers from the adjacent villages were selected randomly to collect data. The SHG members were young, literate, had higher gross annual income (>Rs.60160), having more extension contact than the non-members. The members received loan from financial institutions while the non-members were not received any loan. Likewise, the SHG members were undergoing training on dairy farming while the non-members did not undergo any training till the time of investigation. The milk productivity of cows of SHG members were more in comparison to non-members. Respondents, both members and nonmembers, had less media exposure. The empowerment of SHG members through group activities like meetings, trainings, contacts with change agents, and informal discussion with fellow members contributed in improving members’ socio-economic condition.